2010
DOI: 10.3354/cr00974
|View full text |Cite
|
Sign up to set email alerts
|

Model inter-comparison between statistical and dynamic model assessments of the long-term stability of blanket peat in Great Britain (1940–2099)

Abstract: We compared output from 3 dynamic process-based models (DMs: ECOSSE, MILLEN-NIA and the Durham Carbon Model) and 9 bioclimatic envelope models (BCEMs; including BBOG ensemble and PEATSTASH) ranging from simple threshold to semi-process-based models. Model simulations were run at 4 British peatland sites using historical climate data and climate projections under a medium (A1B) emissions scenario from the 11-RCM (regional climate model) ensemble underpinning UKCP09. The models showed that blanket peatlands are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…-Annual NEE is positively correlated with the length of the growing season. (Dinsmore et al, 2009). The site was drained more than 100 years ago (Leith et al, 2014); the drains have become progressively less effective and re-vegetated over time, leading to slow and progressive rewetting of the site.…”
Section: Helfter Et Al: Drivers Of Long-term Variability In Co 2 mentioning
confidence: 99%
“…-Annual NEE is positively correlated with the length of the growing season. (Dinsmore et al, 2009). The site was drained more than 100 years ago (Leith et al, 2014); the drains have become progressively less effective and re-vegetated over time, leading to slow and progressive rewetting of the site.…”
Section: Helfter Et Al: Drivers Of Long-term Variability In Co 2 mentioning
confidence: 99%
“…As such it is important that 'intact' hydrological regimes are maintained/restored in at risk peatlands (e.g. Clark et al 2010a;Clark et al 2010b) to minimise the impacts of environmental change (Heathwaite 1993). While it should be noted that this study provides data from one blocked gully in 1 year and should be viewed only as a case-study only, these findings do also fit into an increasing body of evidence supporting the practice of gully-/drain-blocking for water-table re-establishment in peatlands (e.g.…”
Section: Water Table Depthmentioning
confidence: 99%
“…During the Medieval warm period between AD 950 and 1100, a decrease in rainfall and an increase in temperature resulted in drying of peat surfaces and promotion of erosion (Ellis and Tallis, 2001;Tallis, 1997). Bioclimatic modelling suggests a retreat of bioclimatic space suitable for blanket peatlands due to climatic change in the 21 st century (Clark et al, 2010;Gallego-Sala et al, 2010;Gallego-Sala and Prentice, 2013). Li et al (2017a) found that future climatic change will begin to affect sediment release from increasingly large areas of blanket peatland in the Northern Hemisphere.…”
Section: Factors Affecting Erosion In Peatlands 41 Climatic Conditionsmentioning
confidence: 99%